Computational approaches to morphology and syntax - Roark, Brian (Oxford surveys in syntax and morphology., 2007)
This book provides a critical and practical guide to computational techniques for handling morphological and syntactic phenomena, showing how these techniques have been used and modified in practice. - ;The book will appeal to scholars and advanced students of morphology, syntax, computational linguistics and natural language processing (NLP). It provides a critical and practical guide to computational techniques for handling morphological and syntactic phenomena, showing how these techniques have been used and modified in practice. The authors discuss the nature and uses of syntactic parsers.